Policy response to COVID-19 shock: measuring policy impacts on lending interest rates with granular data - Dassatti, Cecilia; Mariño, Natalia (Estudios de Economía, 2023)
As a response to the COVID-19 shock, the Uruguayan government expanded an existing public credit guarantee and introduced deductions in local currency reserve requirements. Policies of the same nature were also implemented by several governments throughout the world. This paper contributes to the financial additionality literature and the literature on the bank lending view of the monetary policy by analyzing the impact of this type of policies on loans’ interest rate spread over the interbank rate. Using a very detailed database on loan contracts, we estimate a dynamic panel model to analyze the effects of policy responses to the COVID-19 shock over loan interest rates. We find that the PCG policy had a relatively higher effect on loans’ interest rates in comparison to the reserve requirements policy.